Energy and the environment : cost-benefit analysis : proceedings of a conference held June 23-27, 1975 - Karam, R. A. (Ratib Abraham), 1934-; Morgan, K. Z. (Karl Ziegler), 1908- (Energy (Oxford) : Supplement, 1976)
Energy and the Environment Cost- Benefit Analysis originates from a conference, the objective of which is to set a global standard to measure the cost and benefit of human's production of energy. The book focuses on the analysis of the societal and ecological effects of such a production. It also enumerates some existing sources of energy.